The text is a method of Quranic dialogue in displaying intellectual deviation - Mohamed Ismail Hashem / Ammar Bassem Saleh ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2022)
The Qur’anic dialogue is distinguished by its invitation to all, that is: it is not satisfied with inviting the believers only to it, but rather invites all people to that because of its goodness and righteousness. Moreover, this dialogue does not mean fabrication and sophistry, but rather it is a dialogue based on the conditions of dialogue, its politeness and its horizons. This is confirmed by the Qur’an; The Holy Qur’an has taken dialogue as a way for all of its issues, because it is based on miraculous characteristics and methods that enable it to defame others, and it is also the way to clarify the differences that appear on the tongues of its opponents. After the failure with the interlocutors and their insistence on falsehood with the brightness of the truth, the dialogue is an honest image to reveal the amount and size of the conflict that took place between the opposing parties. The Qur’an also informs us of the reality of the opponent through this dialogue, as he wants to bring the interlocutor and force him to insults, insults and wrong attitudes. However, the Qur’an teaches us how the Muslim does not get dragged behind that, because he possesses calmness and complete mind..., the value of a Muslim appears in how he leads Dialogue in an effective manner commensurate with the atmosphere of dialogue, the Muslim is his concern and starting point in the dialogue is the true message.